Sistem Wi-Fi Coin untuk Optimasi Akses Internet dan Bisnis di Desa Wisata Sanjai Bukittinggi - Arrya Anandika; Rifki Suwandi; Rian Ferdian; Tati Erlina; Ratna Aisuwarya; Budi Rahmadya; Dodon Yendri; Rizka Hadelina; Nefy Puteri Novani; Desta Yolanda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
The problem that occurs in Sanjai Tourism Village is inadequate internet access. Internet access is fundamental nowadays, both in daily activities and in the context of promotional activities for Tourism Villages to attract visitors. One of the aspects of assessing the Indonesian Tourism Village Award is digital creativity. To make this happen, it is necessary to have internet access that everyone can enjoy, including the community, visitors, and the Tourism Village group (Pokdarwis) in the Sanjai Tourism Village. Therefore, in Community Service activities, a Wi-Fi Coin system was designed to improve internet access in the Sanjai Tourism Village. The Wi-Fi Coin System uses coins to access the internet. In addition, the Wi-Fi Coin system can be portable for use in the desired location. The method used consists of three stages: preparation consisting of a survey and needs analysis to obtain data on community needs, especially the Sanjai Tourism Village Pokdarwis. The implementation consists of system design, testing, and implementation. System design and testing were carried out at the Unand Computer Engineering Department. Meanwhile, the implementation was done directly before the Pokdarwis team and the Village Community. Trials and equipment handover to the Sanjai Tourism Village Pokdarwis marked the activity results.